Penerapan ESG dalam Membangun Budaya Perusahaan yang Berkelanjutan di PT Garuda Indonesia Tbk - Arizza Zulia Rahmatul Jannah; Ida Bagus Ketut Bayangkara (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
This study aims to analyze the implementation of Environmental, Social, and Governance (ESG) principles at PT Garuda Indonesia Tbk as a strategy to build a sustainable corporate culture. In the context of corporate growth, ESG implementation is important to maximize corporate value and increase stakeholder trust. This study uses a qualitative method by conducting a literature study on ESG from various sources of previous research journals, articles on the internet and corporate sustainability reports. The results of the study indicate that ESG implementation contributes to improving corporate image, operational performance, and post-crisis reputation. Garuda Indonesia is committed to reducing carbon emissions through fuel efficiency programs and the use of Sustainable Aviation Fuel (SAF), as well as creating a safe and healthy work environment for employees. In addition, the implementation of Good Corporate Governance (GCG) which focuses on ethics, accountability, transparency, and sustainability is an important foundation in the company's operations. This study confirms that the implementation of ESG principles at PT Garuda Indonesia Tbk not only supports corporate sustainability, but also contributes to the achievement of sustainable development goals in Indonesia, making it an example for other companies in integrating social and environmental responsibility into their business strategies.